Pengaruh penggunaan berbagai pupuk organik padat terhadap jumlah daun, jumlah akar dan tinggi batang fodder jagung - Akerina, Hans; Kustyorini, Tri Ida Wahyu; Susanto, Waluyo Edi; Hadiani, Dimas Pratidina Puriastuti (Jurnal Sains Peternakan, 2021)
The purpose of this study was to determine the effect of the use of various solid organic fertilizers on the number of leaves, number of roots and height of corn fodder. The materials used in this study were 3000 corn, rabbit urine, water, soil, vermicompost and manure. The method used was a field experiment using a completely randomized design (CRD) with solid organic fertilizer as treatment, while the research treatments included P0 = 100% soil media, P1 = 90% soil media + 10% vermicompos, P2 = 90 soil media. % + manure 10%, each treatment was repeated 4 times. Variable. research. this. is. number of leaves, number of roots and height of stems. The statistical analysis used was analysis of variance. If there is an influence, it is followed by the LSD test. Based on the results of the study, the effect of the use of various solid organic fertilizers showed that there was a very significant effect (P <0.01) on the number of roots and stem height, but the effect was not significant (P> 0.05) on the number of leaves of corn fodder. The highest value for the number of leaves was found in treatment P1 (1.75 pieces), the highest value for the number of roots in treatment P1 (4.30 leaves) and the highest value for stem height in treatment P1 (2.42 cm). Based on the results of the study, it can be concluded that the using 10% vermicompost fertilizer resulted in the best number of leaves, number of roots and height of the corn fooder